THE INFLUENCE OF INTEREST RATE, MONEY CIRCULATION, INFLATION, AND CPI AGAINST EXPORT AND IMPORT IN INDONESIA 2012-2018 - Sumantri, Fazhar; Latifah, Umi (Jurnal Ekonomi Pembangunan, 2019)
Indonesia?s economic growth can no longer depends on internal trade only but needs to depend on the export and import with the global market, thus macroeconomic influence towards export and import needs further research.Thus, this research focuses on the effect of multiple macroeconomic variables which are the rate of loans, money supply, inflation and consumer price index towards export and import in Indonesia. The data used in this research are secondary data acquired from BPS, BI and the Ministry of Trade during the periode of 2012-2018, which are analyzed using the classic assumption tests (normality test, autocorrelation test, heteroscedasticity test, and multicollinearity test) followed by the multiple regression analysis. Based on the F test we concluded that all the dependent variables are simultaneously effecting both import and export, while the T test shows that only the Consumer Price Index does not have any effect towards both import and export  while the other variables effect both import and export, this signifies that Consumer Price Index does not need to be considered in analyzing and forecasting of both import and export.